The Impact Of The Physical Environment On Tuberculosis In Wonorejo Kediri Regency - Ema Mayasari; Yanuarius Uluk (Master of Public Health Program Universitas STRADA Indonesia, 2023)
The poor of physical environment is the main factor causing the development bacteria of TB (mycobacterium tuberculosis). Mycobacterium tuberculosis will accumulate more and more in a poor environment.The purpose of this study was to determine the impact of the physical environment on the Incidence of Tuberculosis in Wonorejo, Kediri Regency. The research design used was case control with a population consisting of two groups, namely all people with sputum examination results (BTA +) as the case group and people with sputum examination results (BTA -) as the control group. A sample of 40 respondents was taken by simple random sampling. The independent variable is the physical environment of the house (ventilation, floor type and occupancy density) with the dependent variable being the incidence of tuberculosis. Data was collected using observation sheets.The results of the simultaneous analysis show that there is a significant influence between the physical environment and the incidence of TB (p-value = 0.000), while partially the physical condition of the house, namely ventilation, p-value = 0.00 and occupancy density, p-value = 0.044 each had an effect on the incidence of tuberculosis, but the type of floor (p-value = 0.999) had no effect on the incidence of TB. The condition of the house that does not meet the healthy requirements, especially in terms of ventilation and occupancy density, makes the bacteria that cause TB able to live and multiply. is on the decline.